Visual stimulus training and brain function enhancement - Agusteivie Albert Jefta Telew; Fredrik Alfrets Makadada; Fadli Ihsan (Lentera Negeri, 2026)
Visual stimulus training has recently gained increasing attention as a non-pharmacological approach for enhancing cognitive performance and neural efficiency. Modern lifestyles characterized by cognitive overload, prolonged digital exposure, and reduced attentional capacity have contributed to declining cognitive performance among young adults. Visual stimulus interventions are believed to improve attentional control, visuomotor coordination, reaction speed, and executive functioning through neuroplastic adaptation mechanisms. Therefore, this study aimed to investigate the effects of visual stimulus training on brain function enhancement among healthy young adults. This study employed a randomized controlled experimental design involving 40 healthy participants aged 18–25 years. Participants were randomly divided into an experimental group (n = 20) and a control group (n = 20). The intervention consisted of an eight-week visual stimulus training program performed three times per week. Cognitive variables assessed included attention, working memory, reaction time, and executive functioning using standardized computerized cognitive tests. Neurophysiological adaptation was evaluated using electroencephalography (EEG). Data were analyzed using paired sample t-tests and repeated-measures ANOVA with a significance level of p < 0.05. The results demonstrated significant improvements in the experimental group following the intervention. Attention scores increased from 78.40 ± 6.28 to 87.15 ± 5.74 (p = 0.001), while working memory scores improved from 71.85 ± 5.76 to 80.90 ± 5.28 (p = 0.001). Reaction time decreased significantly from 312.25 ± 21.67 ms to 276.10 ± 18.44 ms (p = 0.001). Executive function scores also improved significantly from 74.20 ± 6.12 to 83.45 ± 5.87 (p = 0.001). EEG analysis revealed increased beta wave activity and reduced alpha wave activity after the intervention. In conclusion, visual stimulus training significantly enhanced cognitive performance and neural activation among healthy young adults. The findings suggest that visual stimulus training may serve as an effective and practical strategy for brain function enhancement.